Migraine and erythrocyte biology: a review. (14th March 2014) - Lippi, G.; Cervellin, G.; Mattiuzzi, C.
Summary: Migraine is a common disabling headache disorder that is conventionally classified according to the presence or absence of aura. The pathogenesis of this disorder entails a complex interplay of neurovascular factors, that trigger reduction of cerebral blood flow followed by reactive vasodilatation. Despite major emphasis has been placed on the investigation of putative biomarkers that could predict response to specific treatments and prophylaxis, less focus has been directed at the association between migraine and erythrocytosis. Erythrocytosis is typically accompanied by hyperviscosity, that is now considered a crucial determinant in the pathogenesis of migraine. The results of some epidemiological investigations are in substantial agreement to confirm the existence of a significant relationship between increased haemoglobin levels and migraine, whereas some case reports have also reported an effective improvement of symptoms after reduction of erythrocyte count by therapeutic venesection. Interesting evidence has recently emerged from the assessment of red blood cell distribution width (RDW), a simple and inexpensive measure of anysocytosis that has been also associated with a variety of ischaemic and thrombotic disorders other than migraine. The aim of this review was to provide an overview of the current clinical and epidemiological evidence linking migraine and erythrocyte biology.